2011
DOI: 10.1089/jir.2010.0131
|View full text |Cite
|
Sign up to set email alerts
|

Host Response Cytokine Signatures in Viral and Nonviral Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Viruses are strongly associated with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Interferon-inducible protein-10 has been recently described as a biomarker of human rhinovirus infection, but there are no reports on the role of other immune mediators in AECOPD of viral origin. As an attempt to evaluate the differences in the systemic immune mediators profiles between AECOPD patients with presence/absence of viral infection, we measured 27 cytokines, chemokines, and cellular growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 12 publications
1
23
0
3
Order By: Relevance
“…Similarly, levels of endothelin 1, a potent vasoconstrictor and bronchoconstrictor peptide with important proinflammatory activities in the airways, tend to be higher during COPD exacerbation associated with viral or chlamydial infection, both in sputum and in plasma 212. Virus-induced COPD exacerbations are also associated with increased plasma levels of IL-10, IL-12, and IL-15,213 whereas all COPD exacerbations (with or without respiratory virus isolation) are characterized by increased plasma levels of IL-2, IL-13, and vascular endothelial growth factor 213…”
Section: Cytokines In Copd Exacerbationsmentioning
confidence: 99%
“…Similarly, levels of endothelin 1, a potent vasoconstrictor and bronchoconstrictor peptide with important proinflammatory activities in the airways, tend to be higher during COPD exacerbation associated with viral or chlamydial infection, both in sputum and in plasma 212. Virus-induced COPD exacerbations are also associated with increased plasma levels of IL-10, IL-12, and IL-15,213 whereas all COPD exacerbations (with or without respiratory virus isolation) are characterized by increased plasma levels of IL-2, IL-13, and vascular endothelial growth factor 213…”
Section: Cytokines In Copd Exacerbationsmentioning
confidence: 99%
“…Although individual cytokine signals in early SIV infection have been measured previously, the ability to measure multiple protein analytes simultaneously and sensitively by cytokine bead multiplex assay has allowed a more comprehensive approach to the study of inflammatory mediators in acute viral infections (4,(20)(21)(22). Cytokine multiplex assays have been developed using antibodies against human cytokines that were found to be crossreactive with NHP analytes.…”
mentioning
confidence: 99%
“…In both subgroups, the TNF- α levels declined in the sputum, although the decline in TNF- α blood levels was not significant. Almansa et al [30] and Pinto-Plata et al [31] measured various inflammatory cytokines before and after treatment of AECOPD. Their results showed that serum IL-8 expression was significantly reduced but that TNF- α did not change significantly; these findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%